POLA KONSUMTIF MAHASISWA DI KOTA PEKANBARU - Khoirunnas "; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study was conducted in the city of Pekanbaru province of Riau. The purpose of this research is To know how the consumption of the life of the student City’s Pekanbaru. This study titled “Pola Konsumtif Life Student City’s Pekanbaru province of Riau”. The focus of this research is How the impact of the behavior of konsumtif students against the value of academic as well as the lecture bersistem activities in the city of Pekanbaru. The writer just taking a sample of Research take as much as 5 people students. The writer use a technique Snowball Sampling in determine the respondents in the study. Students who studied is students who have a tendency to make fun of as the purpose of life (hedonism), make a collection of personal as the primary (shopaholic) and the pattern of who knows no bounds (seksualisme). The writer using the thedescriptive kualitatif. Instruments data is observations, the interview, and the documentation. The results of research suggests that In research conducted the researchers found some patterns behavior konsumtif students Riau University namely Pola Konsumtif Shopaholic (On this pattern student is an individual who is very excessive in the use of money, time and of them. Informants dreadfully extravagant in shopping. Not only in belana, informant also involved in the of young people who waste of time for the sake of personal pleasures. The pattern Konsumtif Hedonisme (On this pattern the researchers found that the informant deliberately looking for fun in continuous in order to eliminate the burden of them. Although problems facing the informant is not a problem that should be too to think. Informants just want to fill in the days and time for fun.Keywords: Pola Konsumtif, Pola Konsumtif Life Student